"Awareness to touch": A qualitative study of nurses' perceptions of interpersonal professional contact after an experiential training. (October 2021) - De Luca, Enrico; Fatigante, Marilena; Zucchermaglio, Cristina; Alby, Francesca
Abstract: Aim: This study aimed to explore nurses' perceptions of touch in their professional practice and how these perceptions were articulated in discourse, among participants who attended a specific training on touch and those who did not. Background: Touch is an essential part of nursing practice. Research showed that the use of touch influences patients' general well-being, improving a sense of presence and infusing security and encouragement. Nurses' attitude towards touch influence positively their job satisfaction and reduces burnout syndrome risks. Nevertheless, there are very few studies describing specifically nurses' perceptions and opinions about the use of interpersonal physical contact in the clinical setting. Also, an educational perspective focusing on touch seems missing from nursing curricula and research. Design: A qualitative methodology was adopted. Focus groups were organized to explore how nurses define and interpret touch and its relevance in their professional practice. The findings obtained in a previous quantitative step of this research inspired the formulation of the questions posed to nurse participants. Methods: Six focus groups were conducted in three Italian hospitals, which also hosted a one-day training on touch. For each hospital, a purposive sampling approach was used to organize two focus groups: one was made up of nurses who attended the training, and one was made up of nurses who did not. Qualitative thematic analysis was used to identify recurring patterns of meaning by which touch is discussed and interpreted in the focus groups. Results: Registered nurses (N = 39) from different clinical experiences participated in six focus groups. The analysis identified four themes: 1) Touch preferences, 2) Touch and Contact as a natural dimension, 3) Touch as a "praxis" and 4) Reflexivity on Touch. All six focus groups showed a general awareness of interpersonal touch and discussed it as a highly valorized (personal and professional) dimension. Specifically, the trained nurses showed a greater variety and richness of their lexicon, a semantic and imaginary repository by which they described their experience and competence. Conclusions: This study highlights that nurses consider touch as an important, essential part of their practice. Moreover, it suggests that specific training on interpersonal touch in nursing care facilitate nurses to shift their perceptions from a generic, abstract and "personal" dimension, into an articulated, disciplined and specialized practice. This has implications for education on touch in nursing. Highlights: Touch is considered an unavoidable and inherent aspect of nursing care. Nurses consider touch as either an in-built personal, vocational dimension or a professional, technical skill that may be learnt. Training on touch helps to increase nurses' awareness of their interpersonal skills within professional practice. Including training on touch in educational curricula can promote the integration of relational and technological aspects of nursing care.